On the roots of the substitution Dickson polynomials - Javier Gomez-Calderon (International Journal of Mathematics and Mathematical Sciences)
We show that under the composition of multivalued functions, the set of the y-radical roots of the Dickson substitution polynomial gd(x,a)−gd(y,a) is generated by one of the roots. Hence, we show an expected generalization of the fact that, under the composition of the functions, the y-radical roots of xd−yd are generated by ζdy.